Co-rotational planar beam element with generalized elasto-plastic hinges. (15th November 2017) - Alhasawi, Anas; Heng, Piseth; Hjiaj, Mohammed; Guezouli, Samy; Battini, Jean-Marc
Highlights: A co-rotational planar element with generalized elasto-plastic hinges. An anisotropic super-elliptic yield function to reproduce M-N interaction of cross-section and joints. Consistent integration of the constitutive equations of the hinges. Numerical examples show the influence of the roundness factor on the load carrying capacity. Pinching effect and cyclic softening are also found in the example. Abstract: Slender elements in framed structures may undergo large displacement and experience highly nonlinear behavior. This paper presents a two-node co-rotational flexible beam with generalized elasto-plastic hinges at the beam ends. A Condensation procedure is used to remove the internal degrees of freedom so that the formulation is easily incorporated with the standard co-rotational approach. A family of asymmetric and convex yield surfaces of super-elliptic shape is considered for the plastic behavior of the hinges. By varying the roundness factor, an infinite number of yield surfaces are obtained making it possible to select the yield function that best fit experimental data of any type of cross-section and material. The nonlinear response of bolted connections subjected to both bending and axial forces are conveniently modeled with such a yield surface. Discrete constitutive equations for the hinge plastic deformations are derived using the implicit scheme for both smooth and non-smooth cases. Numerical examples demonstrate the accuracy of the model in predicting the large displacement inelastic response of framed structures. Effect of the roundness factor on the ultimate load strongly depends on the structure typology. It was observed that cyclic loading produces pinching effect, cyclic softening and ductile behavior. Those effects are more pronounced with anisotropic yield criteria.